Building States to Build Peace - Edited By Charles T Call and Vanessa Wyeth (New Dehli Viva Book, 2009)
Explores the core challenges involved in institutionalizing postconflict states. This volume covers the range of the most vexing and diverse problems confronting domestic and international actors seeking to build states while building peace.
Include Index, Bibliography, List of Acronyms and the Contributors.
There is increasing consensus among scholars and policy analysts that successful peacebuilding can occur only in the context of capable state institutions. But how can legitimate and sustainable states best be established in the aftermath of civil wars? And what role should international actors play in supporting the vital process?Addressing these questions, this state-of-the-art volume explores the core challenges involved in institutionalizing postconflict states.
Keywords: Peace-Building -- Peace-Building--Study and YTeaching